Secondary nanoparticle formation by a reaction of ozone and volatile organic compounds emitted from a commercial dishwashing liquid - Thai Phuong Vu; SunHwa Kim; SeungBok Lee; 배귀남 (한국입자에어로졸학회, 2011)
In this study, the formation of nanoparticles by a reaction of ozone with the volatile organic compounds(VOCs) emitted from a commercial dishwashing liquid was investigated using a 1㎥ reaction chamber(1×1×1 m). The dishwashing liquid was found to contain many VOCs, particularly terpenes. Some of these VOCs are known to readily react with ozone, forming indoor secondary pollutants. The correlation of particle concentration and reacted ozone concentration was examined with injections of three different ozone concentrations; 50, 100 and 200 ppb. The secondary nanoparticles were formed faster, with their numbers and mass concentrations becoming higher on increasing the concentration of ozone injected.